2019
DOI: 10.1177/0954411919886763
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament deficiency combined with lateral and/or medial meniscal injury results in abnormal kinematics and kinetics during level walking

Abstract: Anterior cruciate ligament injuries are commonly combined with meniscal tears. This study was performed to analyze the kinematics and kinetics of knees with anterior cruciate ligament deficiency with or without a combined medial or/and lateral meniscal injury during level walking. In all, 29 patients with unilateral anterior cruciate ligament deficiency and 15 healthy male volunteers were recruited. Among these patients, 12 had isolated unilateral anterior cruciate ligament injuries (ACLD group), 5 had combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…ACLD patients combined with higher severity degrees of meniscus tears (e.g., ACLDML vs. ACLDL) exhibited more abnormal knee joint contact forces and moments. These results supported our second hypothesis, which also confirmed previous findings that described the abnormal knee biomechanics after ACL and meniscal injuries during walking [ 16 , 23 ] and ascending stairs [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…ACLD patients combined with higher severity degrees of meniscus tears (e.g., ACLDML vs. ACLDL) exhibited more abnormal knee joint contact forces and moments. These results supported our second hypothesis, which also confirmed previous findings that described the abnormal knee biomechanics after ACL and meniscal injuries during walking [ 16 , 23 ] and ascending stairs [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Various effects of meniscus injuries on knee joint stability showed that a combined ACL and meniscal injuries could alter the biomechanical response in different ways, depending on the type of meniscal tears. Ren et al [ 23 ] demonstrated a combination of “stiffening gait” and “pivot shift gait” patterns in ACLD knees with medial meniscus posterior horn tear, and this abnormal gait was confirmed by Liu et al [ 16 ] in ACLD combined with medial and lateral meniscus injury patients. However, these studies mainly focused on the measurement of kinematics and kinetics during gait [ 16 , 23 , 33 ] and ascending stairs [ 24 , 34 ] rather than running.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The authors found a more posterior tibial translation and internal tibial rotation in the model without menisci. Liu et al ( 24 ) simulated a level walking from gait analysis of ACL-deficient patients with different meniscal lesions (either medial, lateral, and bilateral). Altered kinematics and kinetics were found in the presence of bilateral meniscectomy, with lower abduction-adduction and internal-external moment peaks compared to the control group.…”
Section: Laxitymentioning
confidence: 99%